Lactoperoxidase and lysozyme activity in buff alo milk from Argentine - Van Nieuwenhove, Carina Paola (2004)
Lysozyme (LZ) and lactoperoxidase (LP) activity and thiocyanate (SCN ) content were monitored in the milks - of twelve individual Murrah buffalo during mid-lactation. Samples were pasteurized at low (65ºC, 30min) and high (72ºC, 15s) technique for evaluating heat effect on both enzymes. LP value were 2.49±0.86 U.mL , thiocyanate level -1 8.64 ± 2.08 ppm and LZ activity was 424 ± 349 U.mL . There was difference between heat treatment on both enzymes. -1 LZ was complete inactivated by low and high pasteurization, while LP activity showed 16% of inactivation on low pasteurization and 80% on high pasteurization. SCN content was not modified by any heat treatment. This result - shows that it is convenient to use low temperatures to preserve buffalo raw milk. LP is the most abundant enzymes in buffalo milk, while LZ has very low activity. Addition of SCN or hydrogen peroxide can be carried out when LP is not - limitation factor in buffalo milk.